EMF cancer scares epidemiology versus body power. - Deutsch, S. (IEEE Engineering in medicine and biology magazine)
This essay is about electromagnetic field (EMF) cancer scares. But this essay is different from all of the previous demands for an epidemiological recount. We have been, and will continue to be, in a never-ending war involving epidemiology-population studies that point to an increased risk of cancer, especially childhood leukemia, for those living under the influence of EMFs. But if EMFs cause cancer, the effect is so slight that every epidemiological result is open to statistical question. It remains to be seen if judges and juries will respect the present weight of scientific evidence represented by the ANSI/IEEE levels, or if they will bow to emotional appeals that claim that illness is caused by some external source of energy, such as EMFs